Salvaguarda do Património Urbano Habitacional. Contributos para a Conceção de um Manual de Manutenção da Casa Burguesa do Porto - Joana Carolina Pedra Henriques (2017)
The objective of this dissertation is to contribute to the concept of a future maintenance manual for the bourgeois house of Porto, directed towards the need for the preservation and protection of this built heritage. A revision of the general bibliography on building maintenance was necessary and focused on understanding its main concepts, as well as evaluating its importance over the course of the history of the protection of built heritage, nationally and internationally. The study basically dealt with the maintenance practices in the urban context of the city of Porto and, concretely, on the city's current built environment. As a framework, the main historical documents were analysed that constitute the promotion of habits or maintenance practices promoted by the city government. Next, an analysis was made of the maintenance carried out, during the work and afterwards, by the two main entities that contributed most to safeguarding the built heritage of the city: the CRUARB1 (Commission for the Urban Renovation of the Ribeira/Barredo Area) and the FDZHP2 (Foundation for the Development of the Historic Centre of Porto). In order to understand the maintenance carried out by private initiative, three case studies were analysed, chosen randomly in the city, but which have in common the fact they present a reasonable state of preservation. These examples correspond to bourgeois houses of the 19th century that have distinctly different uses today (a day centre, a guesthouse and a residence) but are still linked to uses for habitation. Lastly, a summary is given of the results obtained in each of the approaches mentioned above, in the expectation that this may contribute to the devising of a future maintenance manual for the bourgeois house of Porto.